Hearing impairment and frailty in later life: The Health in Men Study (HIMS). (February 2022) - Tian, Rong; Trevenen, Michelle; Ford, Andrew H.; Jayakody, Dona M.P.; Hankey, Graeme J.; Yeap, Bu B.; Golledge, Jonathan; Flicker, Leon; Almeida, Osvaldo P.
Highlights: Two measures of frailty, the FRAIL scale and the frailty Index, were used in this study. Hearing impairment was associated with frailty, regardless of its definition. The association between hearing loss and frailty cannot be explained by social isolation alone. The proportion of men with hearing loss increased with increased severity of frailty. Abstract: Objective: To determine if hearing loss is associated with increased risk of frailty in later life. Study design: Cross-sectional study of a community sample of 4, 004 men aged 70 years and above living in the metropolitan region of Perth, Western Australia. Data were retrieved from the Health in Men Study (HIMS) and the Western Australian Data Linkage System (WADLS). Frailty was assessed using the FRAIL scale and the Frailty Index. Hearing loss was defined by self-report or by diagnosis recorded in the WADLS. We also collected demographic, lifestyle and social support information. Main outcome measures: Frailty was assessed using the FRAIL scale and the Frailty Index. Results: The prevalence of frailty in the sample population was 16.1% and 25.4% when assessed using the FRAIL scale and the Frailty Index respectively. After adjusting for participant demographic, lifestyle and social factors, hearing loss was significantly associated with the prevalence of frailty when diagnosed by either measure (FRAIL scale: odds ratio [OR] 1.59, 95 CI% 1.32 to 1.91; Frailty Index: OR 1.76, 95 CI% 1.50 to 2.05). The proportion of men with hearing loss increased with increasing severity of frailty. Conclusion: Hearing loss is associated with increased prevalence of frailty in older men when assessed using the FRAIL scale and the Frailty Index. Future longitudinal studies using objective measures of hearing will be helpful in determining if this association is likely to be causal.